Exploring social policy trajectories in Mainland Tanzania: Driving for gender-inclusive development? - Roosa Lambin; Milla Nyyssölä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
In July 2020, the United Republic of Tanzania gained the status of a lower-middleincome country. This came after two decades of significant social policy reforms and transformations in the country's economic structures. This paper explores social policy trajectories in Mainland Tanzania with a gender lens, to better understand the contributions of these developments to inclusive development. More precisely, we examine past and current policy developments across the areas of health policy, social protection, and employment policy, and the level, reach, and quality of government social policy delivery to working-age women. The paper draws on a scoping review of diverse secondary materials, including academic publications, government policy documents, relevant statistics, and other types of literature. The findings indicate that despite significant advancements in the legal frameworks and increasingly gender-responsive government policy plans, Tanzanian social policy delivery remains two-tiered, with differences in provisions for women in the formal and informal sectors. Additionally, women continue to be largely overlooked in the broader industrialization and development strategy, which hinders the achievement of inclusive development in Tanzania.
Keywords: D63; J16; J68; N37; 330; social policy; gender; Tanzania; inclusive development